Erythema Multiforme-Oral Variant: Case Report (Texas Journal of Medical Science, 2024)
Erythema multiforme (EM) is an interesting dermatologic disease which has oral manifestations. EM is clinically characterized by a “minor” form and a “major” form. It presents a diagnostic dilemma because the oral cavity has the ability to produce varied manifestations. Infections (particularly herpes simplex and mycoplasma pneumonia) and drugs seem to predispose toward the development of EM. The range of possible etiologies for oral disease is immense. Therefore, an otolaryngologist or a dentist while treating such patients should have a differential diagnosis for all oral lesions. We report a case of erythema multiforme in which alcohol (ethanol) seems to be the precipitating factor and have also reviewed the English literature in the present context.